Evaluation of Antimicrobial Potential of a Gel loaded with Silver Nanoparticles of Argemone mexicana for Topical Application - Mohanty, Sudipta Kumar; Panda, Debabrata; Panda, Sasmita; J, Hemalatha; V, Sriharsha D; M, Ashwini (International Journal of Membrane Science and Technology, 2023)
Argemone mexicana is widely known for its antibacterial potential in the traditional system of medicine. With this background, the present study was designed to formulate a gel incorporated with nanoparticles synthesized from Argemon mexixana for topical application. Green synthesis of nanoparticles was carried out from the whole plant extract and latex of A. mexicana. The biosynthesized nanoparticles were characterized by SEM-EDAX, HR-TEM, SAED, XRD before it was incorporated into the gel. The biosynthesized nanoparticles were found to be stable, uniform, spherical, and ranged from 9.21nm to 14.03nm in size. The SAED pattern reveals the presence of a varying degree of crystallinity of nanoparticles. The physicochemical parameters of the gel such as pH, homogeneity, grittiness, viscosity, spreadability, and extrudability were characterized. Both the formulation showed the nanoparticles are well dispersed in the gel with pH (6.90, 6.92), viscosity (1542 scps, 1583 scps), spreadability (5.7 cm/sec, 5.90.1 cm/sec), and extrudability of 86% and 89% respectively. The gel loaded with nanoparticles exhibited strong antimicrobial potential against Escherichia coli, Bacillus subtilis, Staphylococcus aureus as compared to the crude form of the plant extract and latex. Among the two formulations, the highest zone of inhibition (22mm, 16mm, 13mm) was observed by the gel incorporated with methanol extract nanoparticles. Our result demonstrates the nanoparticulate gel of A. mexicana can be effectively used as topical gel for gram positive and negative bacterial infection.